Long‐term efficacy and safety of ustekinumab in 122 refractory Crohn's disease patients: a multicentre experience. Issue 5 (8th January 2018) - Wils, P.; Bouhnik, Y.; Michetti, P.; Flourie, B.; Brixi, H.; Bourrier, A.; Allez, M.; Duclos, B.; Serrero, M.; Buisson, A.; Amiot, A.; Fumery, M.; et al.
Summary: Background: Long‐term outcome of ustekinumab in Crohn's disease (CD) has not been evaluated. Aim: To evaluate the long‐term efficacy and safety of ustekinumab and identify the predictive factors of ustekinumab failure‐free persistence in a cohort of anti‐TNF refractory CD patients. Methods: We performed a retrospective multicentre cohort study including all consecutive CD patients who began subcutaneous ustekinumab and presented a clinical response (defined as a significant improvement of CD‐related clinical symptoms assessed by the patient's physician leading to continued ustekinumab) during the first year of treatment. Primary outcome was treatment failure defined as withdrawal of treatment due to loss of response, intolerance or need for surgery. Results: Eighty‐eight of the 122 (72%) CD patients beginning ustekinumab from March 2011 to December 2014, responded to ustekinumab and were followed up until November 2016. Median time on ustekinumab was 26.6 (13.4‐34.4) months. Forty‐seven patients (54%) continued ustekinumab with a clinical response and 38 (43%) stopped treatment (32 for failure, five for remission and one for pregnancy). Endoscopic response was observed in 82% of patients with endoscopic evaluation and mucosal healing in 39%. Ustekinumab failure‐free persistence rates were 78% at 12 months, 66% at 24 months and 55% at 36 months. No predictive factor of ustekinumab failure‐free persistence was identified. One severe adverse event was observed (anal adenocarcinoma). Conclusion: In this cohort of refractory CD patients receiving long‐term ustekinumab therapy, more than 50% of patients continued ustekinumab treatment with no loss of response, intolerance or surgery and with a good safety profile.